A Challenge for Uridine Derivatives as Inhibitors against SARS-COV-2 Main Protease - Sarkar M. A. Kawsar (New Advances in Medicine and Medical Science Vol. 4, 2023)
This study is focused on the identification of uridine derivatives with the aim of expediting the identification of specific drugs for the treatment of COVID-19. Nucleoside derivatives highly contribute to pharmaceutical and clinical fields as medicinal agents. Various clinical trials are currently underway to identify specific drugs for the treatment of novel global threat viruses. The main protease of SARS-CoV-2 is a significant target for the design and amplification of antiviral drugs. In this investigation, we optimized a nucleoside, uridine, and some of its acylated derivatives (2-14) by employing density functional theory (DFT) at the B3LYP/3-21G level of theory. In the following analysis, the charge distribution, polarizability, and thermodynamic properties such as free energy, heat capacity, and entropy of modified compounds were investigated to determine how certain groups (aliphatic and aromatic) influence drug properties. All derivatives were found to be thermodynamically more stable than the parent ligand uridine, with some being more chemically reactive than others. To investigate drug interactions with receptor proteins, molecular docking methods are the most suitable tools. The blind docking method employs a search throughout the whole surface of the protein molecule for binding sites. Then, molecular docking was performed against the SARS-CoV-2 main protease (PDB: 6Y84 and 6LU7) to investigate the binding mode(s) and binding affinities of the selected uridine derivatives. In the present study, thirteen uridine derivatives with different aliphatic and aromatic chains (2–14) were designed, and a quantum chemical study was performed to determine their thermochemical properties. Most of the compounds studied here could bind near the crucial catalytic residues, HIS41, and CYS145 of the main protease and were surrounded by other active site residues, such as GLY143, MET49, MET165, HIS163, PRO168, GLU166, GLN189, and SER144. Significant binding affinities (-6.0 to -7.8 kcal/mol) for 6LU7 and (-5.9 to -7.7 kcal/mol) for 6Y84 were found, which revealed the potency of inhibition of uridine derivatives against SARS-CoV-2 Mpro. It was resolved that most of the selected uridine derivatives show promising activities and could be used to design effective antiviral drugs against SARS-CoV-2. Finally, all the modified uridine derivatives were analyzed in silico for ADMET and drug-like properties. Overall, the present study might be challenging and helpful for the development of novel uridine-based potential inhibitors against SARS-CoV-2 Mpro.